Phase transitions in some Dicke-type models - Pimentel, B. M.; Zimerman, A. H. (Springer Nature, 1975)
Using the «gap equations», we calculate the thermodynamic properties of the models A, B, C considered by Hioe as well as the Dicke model modified by acoustic phonons according to Thompson. © 1975 Società Italiana di Fisica.